ONLINE WORKSHOP ON EARTH AND SPACE SCIENCES - ATMOSPHERIC PHYSICS AND CLIMATE Proceedings Book 2020 - Costa, Maria João (2020)
This book was produced in the scope of the Curricular Unit Seminar I (Physics of Atmosphere and Climate) of the PhD program in Earth and Space Sciences, which included the organization of the 2020 edition of the Online Workshop on Earth and Space Sciences - Atmospheric Physics and Climate of the University of Évora. This volume brings together the research articles produced by students who attended the course. Since its first edition in 2013, the Workshop has been a space for sharing knowledge and training in science communication. In this sense, it seeks to provide students who attend Seminar Units with an effective experience not only in the preparation and presentation of oral communications and research articles, but also in the organization of the event itself. In the 2020 edition, which took place on June 4, 11 abstracts were submitted and presented, covering the various themes of the PhD program, in addition to two invited lectures.